Optimization of Batch Extraction of Aromatics from Reformed Heavy Naphtha by Response Surface Methodology - Marwa Asad Salih; Raghad F. Almilly (Tikrit Journal of Engineering Sciences)
This study presents an optimization approach for batch extraction of aromatics from reformed heavy naphtha, provided by Al-Dora refinery in Iraq, using furfural solvent. Response Surface Methodology (RSM) based on Box–Behnken design (BBD) was employed to design the experiments to optimize the extraction efficiency and reduce energy consumption in the range of study. The effects of such variables as solvent-to-feed (S/F) ratio (0.5-2.5 vol/vol), stirring speed (200-1000 rpm), and contact time (1-5 h) at an ambient temperature of 20 °C were investigated. Following a (BBD), fifteen experimental runs systematically optimized the extraction efficiency and determined the interactive effects of these variables on extraction efficiency. Experimentally, the percentage efficiency of extraction ranged between 42.77% and 98.01%, pointing to an effective extraction process using furfural solvent. The maximum experimental extraction efficiency of 98.0127% was achieved at an S/F ratio of 0.5, a stirring speed of 1000 rpm, and a contact time of 3 hours. The resulting model was a quadratic polynomial that accurately captured the relationship between process variables and the extraction concentration of aromatics. Statistical analysis demonstrated that the S/F ratio and its squared term significantly influenced the actual concentration. Analysis of variance (ANOVA) showed excellent agreement between experimental and predicted aromatics concentrations. The results obtained by batch experiments will be used later in an intensified continuous extraction operation.